Risk factors and racial disparities related to low maternal birth satisfaction with labor induction: a prospective, cohort study - Rebecca F. Hamm; Sindhu K. Srinivas; Lisa D. Levine (BMC, 2019)
Abstract Background Decreased birth satisfaction has been associated with labor induction. Yet, there is a paucity of data evaluating risk factors for decreased satisfaction associated with labor induction. We aimed to determine what factors impact low birth satisfaction in labor induction and evaluate racial disparities in birth satisfaction. Methods We performed a prospective cohort study of women with term, singleton gestations undergoing labor induction at our institution from Jan 2018 to Jun 2018. Women completed the validated Birth Satisfaction Scale-Revised postpartum, which is subdivided into 3 domains: (1) quality of care provision, (2) women's personal attributes, and (3) stress experienced during labor. A total satisfaction score above the mean was classified as "satisfied", and below as "unsatisfied." Domain and item scores were compared by race. Results Three hundred thirty of 414 (79.7%) eligible women were included. There was no significant difference in birth satisfaction by age, body mass index, Bishop score, or labor induction agent. Black women were 75% more likely to be unsatisfied than non-Black women (54.0% vs. 37.2%, OR 1.75 [95% CI 1.11-2.76], p = 0.037), nulliparas were 71% more  likely to be unsatisfied than multiparas (54.2% vs. 40.9%, OR 1.71 [95% CI 1.09-2.67], p = 0.019), and women whose labor resulted in cesarean birth were almost 3 times more likely to be unsatisfied than women with a vaginal birth (67.4% vs. 42.3%, OR 2.82 [95% CI 1.69-4.70], p < 0.001). Additionally, increased labor length quartile was associated with decreased satisfaction >(p = 0.003). By race, domain 3 scores, which reflect preparedness for labor, were lower for Black women. No differences were seen for domain 1 or 2. Conclusions Black race, cesarean birth, and increasing labor length were identified as risk factors for low birth satisfaction among women who underwent labor induction. Further studies should explore interventions to target women at risk for low birth satisfaction.